Pemberdayaan Peternak Kambing Umbaran di Bantul Berbasis IoT untuk Meningkatkan Produktivitas - Kuswanto, Jeki; Riasasi, Widiyana; Dewi, Melany Mustika; Wasiso, Ichsan (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2025)
The development of Internet of Things (IoT) technology offers new opportunities for managing small-scale livestock farming, including goat farming. The partner of this program, the Umbaran Goat Farmers Group in Bantul, still faces several challenges such as a high mortality rate (12%), inefficient manual feeding, limited digital record-keeping, and marketing that relies solely on local collectors. This community service program aims to improve farm productivity through the application of IoT integrated with a digital farm management system. The implementation method included socialization, workshops, theoretical and practical training, and the deployment of technologies such as a web-based farm management platform, RFID identity tags, and an automatic feeding device. A seven-day trial of the automatic feeder resulted in a total feed distribution of 67 kg, with an average of 9.57 kg/day, and demonstrated a feed saving of approximately 12.99% compared to manual methods. The system also successfully maintained feeding schedule consistency twice a day with 100% accuracy. The results indicate improved efficiency, regularity in feeding patterns, and support for digital transformation in livestock management. Therefore, the implementation of IoT in goat farming not only reduces operational costs but also opens opportunities for developing sustainable business models through the integration of digital systems and online marketing.